ARTIFICIAL INTELLIGENCE IN EDUCATION: OPPORTUNITIES, CHALLENGES, AND PROSPECTS - Kulmamatova Shakhnoza; Zaripova Malika (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This thesis explores the integration of Artificial Intelligence (Al) in the education sector, focusing on its applications, benefits, risks, and potential in Uzbekistan. It examines how Al enhances personalized learning, automates assessment, and supports both teachers and students. The work also addresses the challenges such as data security, reduced human interaction, and the digital divide. Furthermore, the thesis outlines strategic steps for the effective adoption of AI technologies in Uzbekistan’s education system, including infrastructure development, teacher training, and legal frameworks.